Validity and reliability of the happiness scale for adolescents in Yogyakarta - Sintia Gumara Dini (Department of Psychology, Universitas Negeri Yogyakarta, 2018)
Happiness is a subjective concept because every individual has a different benchmark. Nolen-Hoeksema (1998) argues that adolescents have a higher level of depression than adults, who tend to show lower levels. For that reason, there needs to be a scale to measure happiness in adolescents. This research aims to construct a happiness scale for adolescents in Yogyakarta to measure the level of happiness of adolescents in Yogyakarta in a valid way because not all measurement tools used in western cultures can be implemented in the east. This research uses a constructed psychological measurement tool. This research involves 120 adolescents aged 16-18 years in Yogyakarta. In the factorial validity test or factor analysis, there are several items separated from the initial indicators that form new indicators. These, however, are still able to uncover the aim of constructing the scale. From the 60 items proposed, five items were rejected, and 55 others were considered appropriate. Reliability testing yields a result of 0.936, meaning that the scale has a sufficient level of reliability.